Pembelajaran Membuat Resensi Drama dengan Teknik Think Talk Write pada Siswa Kelas XI Bahasa SMA Negeri 1 Cileunyi, Bandung - Al Gadri, Henri Henriyan (Jurnal Artikula, 2018)
This study discusses about the ability of researchers and students in learning to make drama reviews with think talk write technique. The aim of this study is to get an overview of the ability of researcher in the planning and implementation of learning, the ability of students to review drama and the effectiveness of think talk write technique used in learning to make drama reviews. The method used in this study is a quasi-experimental method. The result of this study shows that the researcher is able to carry out learning to review drama with think talk write technique, which is proven by the value obtained at 3.68 with a percentage of 92.25%, students are able to make drama reviews with think talk writing techniques as evidenced by the average score of 4.2 and the average value of post-test 8.45 with a difference of 4.2, and think talk write techniques is effective to use in learning drama review based on the tcount test of (5.67) ttable of (2.04) at the significance level of 5% with a confidence level of 95% of the degree of freedom 19.